Theoretical Connotation and Mechanism Construction of Digital Justice - Hui Ding (Studies in Law and Justice, 2024)
With the development of artificial intelligence, the era of big data has come, and digital technology is changing the traditional way of life. The “online dispute resolution mechanism” based on the theory of “digital justice” has become a new type of dispute resolution that helps and promotes the realisation of justice. However, the theory of digital justice in the help of “close to justice” “to achieve justice” at the same time due to the rationality of the data computation there are also some shortcomings, in order to be more standardised and rational use of digital technology to achieve justice, the need for digital justice governance structure for the optimisation and construction.